Genre_Based SFL Analysis of Academic Writing in English: Investigating Linguistic Features and Genre Conventions in Student's Essay - Mustafa, Mutakhirani; Syihabuddin; Syahriani, Irma (UIN Alauddin Makassar, 2023)
This study aims to conduct a genre-based and systemic functional linguistic (SFL) analysis of academic writing in higher education, with a focus on linguistic features and genre conventions in student essays. The research method used in this study is qualitative research. Specifically, the study uses a case study research design, where the focus is on a single limited case (in this case, student essays in academic writing in higher education). The research method involves collecting and analyzing data through a systematic and detailed examination of the linguistic features and genre conventions of student essays focus on how the students build the coherence and cohesion in academic writing. This research uses a genre-based approach to investigate how students use language to achieve communication goals in academic writing. The study utilizes corpus data from student essays to explore patterns and structures of academic discourse in various genres, as well as to identify linguistic features and coherence and cohesion that distinguish each genre and the researcher implemented interview to the students with six question related to the main research. The results of the study indicated that academic writing in higher education was characterized by a number of typical linguistic features in each genre, which were reflect different conventions and expectations in various academic genres. This study contributes to our understanding of how students use language to convey their ideas and arguments in various academic genres, as well as providing insights into the linguistic features and coherence and cohesion of writing that are important for successful academic writing in higher education. Keywords: SFL, Linguistic Features, Coherence and Cohesion, Essays